Physiological sway of aging on oxidative stress and levels of some minerals in diabetes type II of both female and male in Sulaimaniyah city - Maya Al-samman (College of Education for Pure Sciences, 2020)
Abstract Diabetes is a metabolic disorders disease characterized by the abnormal high levels of blood sugar due to incomplete or relative deficiency of insulin secretion as well as disorders in carbohydrate, lipid and protein metabolism. The study aims to evaluate the physiological effects of aging on oxidative stress and mineral levels in diabetes type II by measuring F.B.S,HbA1c%, levels of a number of important indicators of oxidative stress, level of ferritin ,copper and zinc in the serum. The study included the collecting of 70 blood samples from patients with NIDDM for both sexes in the center of Diabetes and Endocrinology in Sulaimaniyah city. The age of each group in this study ranged between 40-70 years. The study concluded that the rate of both FBS and T.GSH increased with age in diabetic females, the MDA increased with age in diabetic males, and ferritin increased with age in both sexes. Moreover copper decreased with age in diabetics for both sexes.